A233 BASELINE BOWEL ROUTINE AND OTHER PREDICTORS OF BOWEL PREPARATION IN PATIENTS UNDERGOING OUT-PATIENT COLONOSCOPY; RESULTS FROM A PROSPECTIVE SINGLE-CENTRE STUDY. (15th March 2019) - Khan, K; Nehvi, A; Khan, M; Fergani, H; Ganguli, S; Jalali, S; Morgan, D; Spaziani, R; Tsoi, K; Armstrong, D
Abstract: Background: Bowel preparation is essential as a quality measure of colonoscopy. Many studies have reported factors associate with a good bowel preparation but few have evaluated the effect of baseline bowel habit as a predictor. Aims: We aimed to identify factors associated with a good bowel preparation. Specifically, we wanted to determine if baseline bowel habit predicted response to bowel preparation and how accurate patient perception of their bowel preparation was compared to a standard bowel prep score. Methods: Prospective data was collected from out-patients undergoing colonoscopy in the form of a survey in the waiting room of the endoscopy unit. Data included baseline patient and endoscopy factors, and was compared to endoscopist reported Ottawa Bowel Preparation Score (OBPS) to look for correlation in a statistical analysis. Results: Data were available for 243 patients; mean age 57 years, 46% male, 51% had more than a high school education. PEG-Lyte solution (4L) was used for bowel preparation by 48 (19.8%) and sodium picosulfate by 190 (80.2%). The mean OBPS was 3.48 +/- 2.47 SD. The baseline Bristol Stool Form Score (BSFS) was 1–2 in 13%, 3–5 in 74%, and 6–7 in 13% of patients, but BSFS did not predict a better OBPS (p=0.82). The mean times from the patients' last fluids and last solids food to colonoscopy was 5.47 +/- 5.0 and 27.8 +/- 4.8 hours respectively, but neither was a significant predictor of better bowel prep. More procedures were in the afternoon (78%) but there was no difference in the OBPS in the morning and afternoon (Mann-Whitney test, p=0.47). Self-assessment of the quality of bowel preparation was not correlated with OBPS (Spearman rho 0.03, p=0.63), but a patients' level of concern with not having a clean enough preparation was correlated with a worse OBPS (Spearman rho -0.175, p=0.012). The only significant predictor in a univariate analysis was bowel preparation type with sodium picosulfate being significantly better (Mann Whitney test, p<0.01) and this was also seen in preliminary multi-variate regression analysis (p=0.037). Conclusions: In this small prospective study, many of the factors presumed to be requisites for good bowel preparation – time from last food or fluid intake to colonoscopy, baseline stool form, self-reported bowel preparation score, patient demographics – were not correlated with a high quality OBPS. The only identified predictor of better bowel preparation score was the type of prepration, sodium picosulfate being significantly more effective than PEG electrolyte solution. Funding Agencies: None